2015
DOI: 10.1186/s12984-015-0001-0
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal characteristics of gait as outcome measures in multiple sclerosis (EDSS 0 to 6.5)

Abstract: BackgroundGait impairment represents one of the most common and disabling symptom of multiple sclerosis. Quantification of the gait is an important aspect of clinical trials. In order to identify which temporal or spatial parameters of gait could be used as outcome measures in interventional studies of patients with different levels of disability, we evaluated characteristics of these parameters in MS patients across the whole spectrum of mobility from EDSS 0 to 6.5.MethodsThis is a cross-sectional study of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
56
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 21 publications
4
56
0
1
Order By: Relevance
“…Numerous studies have examined gait characteristics in PwMS [3][4][5][6] confirming that PwMS walk slower with decreased stride lengths [3,4], reduced knee and ankle motion [5] and elevated variability [6] compared to healthy controls. Research studies have also established that gait parameters change throughout the disease process.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Numerous studies have examined gait characteristics in PwMS [3][4][5][6] confirming that PwMS walk slower with decreased stride lengths [3,4], reduced knee and ankle motion [5] and elevated variability [6] compared to healthy controls. Research studies have also established that gait parameters change throughout the disease process.…”
Section: Introductionmentioning
confidence: 97%
“…Lizrova- Preiningerova et al (2015) in a cohort of 284 PwMS reported that velocity of gait and step lengths decrease with increasing neurological disability levels [3]. Gait deterioration in MS is generally explained as a consequence of variable neurological deficits such as motor weakness, spasticity, ataxia and sensory disturbance [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The resulting impairments can be relative muscle weakness, sensory deficits, spasticity, and fatigue interfering with different aspects of the walking function such as endurance, muscle coordination, and balance with negative impact on activities of daily living (Cattaneo et al, 2014; Frank and Larimore, 2015; Michailidou et al, 2015). Despite the high prevalence of gait disorder in PwMS, there are relatively few reports describing gait parameters and overall these studies have reported slower walking with shorter stride length and prolonged double support phase, independently of their walking speed (Benedetti et al, 1999; Martin et al, 2006; Givon et al, 2009; Cameron and Wagner, 2011; Kasser et al, 2011; Remelius et al, 2012; Lizrova Preiningerova et al, 2015). It has been suggested that these alterations from speed-matched normative values of healthy persons are part of protective strategies used by PwMS to reduce the risk of falling while walking.…”
Section: Introductionmentioning
confidence: 99%
“…The gait of people with MS compared to healthy individuals is characterised by reduced walking speed [2][3][4][5][6][7], which may be due to decreases in cadence [4,7],stride length [2,3,7] or step length [4,5,7]. Walking speed has been shown to progressively decrease with disease severity in part due to concomitant decreases in step length [8]. Reduced walking speed is also likely a strategy to counter impaired balance, which is common in people with MS [9], by prolonging periods of double support during stance [2,3,7].…”
Section: Introductionmentioning
confidence: 99%